Electrochemical characterization of mangrove sediments: A proposal of new proxies for organic matter oxidation - Cebrián-Torrejón G. (2019)
AP is supported by the “ Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica ” (Fondecyt - Peru), through the MAGNET research program. The collection of sampling was carried out within the framework of the “Impacto de la Variabilidad y Cambio Climático en el Ecosistema de Manglares de Tumbes” project. Supported by the International Development Research Centre of Canada under management of the Instituto Geofísico del Perú (IGP). WM is supported by research grants from the Brazilian Research Council (CNPq) . CJS is supported by the Australian Research Council ( DE160100443 , DP150103286 and LE140100083 ), in cooperation with Universidade Federal Fluminense . Project CTQ2011-28079-CO3-02 which is also supported with ERDF . We would like to thank Kelly Ronchi for the language revision.